Creative and Innovative Ways of Teaching English In Rural Area Through ICT - Dailin Dailin; Melati Melati; Adetio Zayadi (English Education Study Program Faculty of Teacher Training and Education, 2019)
Nowadays, information and communication technology has been growing rapidly. It is used widely in all sectors in the world. In education, ICT has the important role to faster the development of knowledge. But, we should realize that there are still many regions in Indonesia which the application of ICT is not available yet. This paper examines the ways of English teachers used in teaching and learning English in term of ICT implementation especially in two rural areas of Indonesia. This paper also argues some creative and innovative ways that can be practiced in each of those areas. This paper through qualitative approach finds out that the applying of ICT or technology in teaching and learning English cannot be the same for all regions including urban, rural, and remote areas. It can be practiced differently based on the condition of the area. So, the teacher should know the creative and innovative ways of ICT implementation in teaching and learning English.